Analisis Patriarki, Partisipasi Politik, dan Kewarganegaraan Aktif di ASEAN - Anak Agung Mia Intentilia (Intermestic: Journal of International Studies, 2020)
By analyzing to what extent does patriarchy hinders women's political participation, this paper discusses the relation of patriarchy and active citizenship for women in ASEAN member states. For the purpose of analysis, this paper uses the theory of patriarchy and the theory of active citizenship related to politics, gender, and citizenship aspects by using qualitative method and literature analysis. This paper finds that patriarchal culture has a significant impact in hindering women's political participation because it has been institutionalized through: (i) political party practices; (ii) tradition, religion, and customary laws; and (iii) gender segregation in the society. Since the political participation is limited, therefore, the â€œexclusionâ€ of women in the society within ASEAN member states remains. They belong to the marginalized group and are unable to access equal power and resources to act their active citizenship.